Soluciones geotécnicas aplicadas a suelos licuables para mejorar el comportamiento mecánico de cimentaciones superficiales - Almeida Burgos, Jorge Luis (2025)
The design and construction of appropriate foundations is one of the most critical aspects of civil engineering, as it ensures the stability and durability of structures. The bearing capacity of the soil, which refers to the ground's ability to support applied loads without experiencing excessive deformation or failure, is fundamental in determining the most suitable type of foundation. A geotechnical study of the soil is essential to understand its characteristics, such as strength, cohesion, density, and susceptibility to phenomena like liquefaction, which can seriously affect the stability of a structure. In regions like Guayaquil, located in seismic zones and with soils of low bearing capacity, the risk of soil liquefaction is considerable, especially during low to moderate intensity earthquakes. This phenomenon—where poorly consolidated granular soils temporarily lose their shear strength due to seismic activity—can cause foundation failures and compromise the structural integrity of buildings……….